"People of God" in Paul: reflections in conversation with Eckhard Schnabel - Sumney, Jerry L. (Stone-Campbell journal, 2008)
In response to Eckhard Schnabel's reconstruction of the earliest church's understanding of Torah observance in the church, this essay argues that Paul and the Jerusalem church came to recognize multiple ways to embody faith in Christ. Their discussions of Scripture and their experience of the Spirit led them to discern that different observances were appropriate for different ethnic groups. Paul argued for this diversity by insisting that the central and dominant identity of all must be their membership "in Christ".